2021
DOI: 10.1158/1078-0432.ccr-21-0315
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Sirolimus Does Not Improve Outcome in Pet Dogs Receiving Standard-of-Care Therapy for Appendicular Osteosarcoma: A Prospective, Randomized Trial of 324 Dogs

Abstract: The mTOR pathway has been identified as a key nutrient signaling hub that participates in metastatic progression of high-grade osteosarcoma. Inhibition of mTOR signaling is biologically achievable with sirolimus, and might slow the outgrowth of distant metastases. In this study, pet dogs with appendicular osteosarcoma were leveraged as high-value biologic models for pediatric osteosarcoma, to assess mTOR inhibition as a therapeutic strategy for attenuating metastatic disease progression.Patients and Methods: A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…Several studies have demonstrated that cancer cells have a particularly heightened dependence on proteasomes, given their increased expression of mutated proteins and excessive protein synthesis due to aneuploidy [ 54 ]. This suggests that cancer cells are particularly sensitive to proteasome inhibition which can lead to fatal consequences [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that cancer cells have a particularly heightened dependence on proteasomes, given their increased expression of mutated proteins and excessive protein synthesis due to aneuploidy [ 54 ]. This suggests that cancer cells are particularly sensitive to proteasome inhibition which can lead to fatal consequences [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…To augment the rigour and reproducibility of these translational clinical trials, the COP has established the Comparative Oncology Trials Consortium, a network of academic veterinary oncology centers working together to garner information on the efficacy of novel therapeutics 54 . In conjunction with the Morris Animal Foundation (https://www.morrisanimalfoundation.org/), this program has facilitated immuno‐oncology trials including the evaluation of a recombinant, attenuated Listeria monocytogenes expressing a chimeric human HER2/neu protein as an adjuvant therapy in dogs with osteosarcoma (COTC026), the results of which will be compared against a prospective cohort of dogs treated with standard of care carboplatin chemotherapy (COTC022) 55 . Additional philanthropic and governmental efforts to provide immunotherapy for dogs include the V foundation (https://http://www.v.org), the American Kennel Club Canine Health Foundation (https://www.akc.org), and the Pre‐medical Cancer Immunotherapy Network Canine Trials (PRECINCT, https://www.precinctnetwork.org).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this project reported a multicenter, randomized, prospective clinical trial focused on the use of a mammalian target of rapamycin (mTOR) inhibitor, sirolimus in 324 dogs with osteosarcoma treated with amputation and chemotherapy. However, the results showed no advantage with the use of sirolimus, but this is a good example of a preclinical clinical trial for drugs aimed to treat osteosarcoma [38].…”
Section: Animal Models For Cancer Researchmentioning
confidence: 92%